Honey on the Page : A Treasury of Yiddish Children's Literature - Udel, Miriam; Udel, Miriam (Book collections on Project MUSE., 2020)
An unprecedented treasury of Yiddish children's stories and poems enhanced with original illustrations. While there has been a recent boom in Jewish literacy and learning within the US, few resources exist to enable American Jews to experience the rich primary sources of Yiddish culture. Stepping into this void, Miriam Udel has crafted an exquisite collection: Honey on the Page offers a feast of beguiling original translations of stories and poems for children. Arranged thematically--from school days to the holidays--the book takes readers from Jewish holidays and history to folktales and fables, from stories of humanistic ethics to multi-generational family sagas. Featuring many works that are appearing in English for the first time, and written by both prominent and lesser-known authors, this anthology spans the Yiddish-speaking globe--drawing from materials published in Eastern Europe, New York, and Latin America from the 1910s, during the interwar period, and up through the 1970s. With its vast scope, Honey on the Page offers a cornucopia of delights to families, individuals and educators seeking literature that speaks to Jewish children about their religious, cultural, and ethical heritage. Complemented by whimsical, humorous illustrations by Paula Cohen, an acclaimed children's book illustrator, Udel's evocative translations of Yiddish stories and poetry will delight young and older readers alike.